Forecasting the monsoon on daily to seasonal time‐scales in support of a field campaign. (20th October 2019) - Martin, Gill M.; Brooks, Malcolm E.; Johnson, Ben; Milton, Sean F.; Webster, Stuart; Jayakumar, A.; Mitra, Ashis K.; Rajan, D.; Hunt, Kieran M. R.
Abstract : The successful planning and execution of a major field campaign relies on the availability and reliability of weather forecasts on a range of time‐scales. Here, we describe the wide range of forecast products generated in support of a field campaign that took place in India in 2016 as part of the Interaction of Convective Organization with Monsoon Precipitation, Atmosphere, Surface and Sea (INCOMPASS) project. We show examples of the suite of plots generated every day from the forecasts and supplied to the mission scientists, and describe how these were used to plan the flights. We highlight the benefits of having access to forecasts from a range of model resolutions and configurations; these allowed judgements to be made about uncertainty, particularly in the amount and location of deep convective rainfall, which is an important consideration for flight planning. Finally, we discuss the legacy of the forecasting activity, which has not only advanced our understanding of monsoon forecasting but also created a large database of targeted model forecast products for the whole of the 2016 monsoon season. These can be used by researchers for comparisons with in situ observations as well as future modelling studies. Abstract : The successful planning and execution of a major field campaign relies on the availability and reliability of weather forecasts on a range of timescales. We use three case studies to illustrate how access to multiple forecast products from a variety of model configurations at a range of resolutions contributed to successful flight planning for the Interaction of Convective Organization with Monsoon Precipitation, Atmosphere, Surface and Sea (INCOMPASS) field campaign in India in 2016.